2021
DOI: 10.3389/fphar.2021.723922
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Ameliorated Intermittent Hypoxia-Aggravated Endothelial Barrier Disruption and Atherosclerosis via the cAMP/PKA/RhoA Signaling Pathway

Abstract: Background: Endothelial barrier dysfunction plays a key role in atherosclerosis progression. The primary pathology of obstructive sleep apnea-hypopnea syndrome is chronic intermittent hypoxia (IH), which induces reactive oxygen species (ROS) overproduction, endothelial barrier injury, and atherosclerosis. Salidroside, a typical pharmacological constituent of Rhodiola genus, has documented antioxidative, and cardiovascular protective effects. However, whether salidroside can improve IH-aggravated endothelial ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 57 publications
(81 reference statements)
3
17
0
Order By: Relevance
“…Our results are consistent with previous studies, out of the IH context, which demonstrated that the inhibition of VE-cadherin cleavage [37], tyrosine-kinases [37,38], src-kinases [39,40] and HIF-1 [41,42] protects against atherosclerosis in ApoE-/-mice. However, we could not exclude the contribution of other pathways activated by IH, such as cAMP/PKA/RhoA [19], inflammation [10,43], NF-kB/TNFα pathways [16,27], cysteinyl-leukotriene pathway [44] and cyclooxygenase pathway [45].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results are consistent with previous studies, out of the IH context, which demonstrated that the inhibition of VE-cadherin cleavage [37], tyrosine-kinases [37,38], src-kinases [39,40] and HIF-1 [41,42] protects against atherosclerosis in ApoE-/-mice. However, we could not exclude the contribution of other pathways activated by IH, such as cAMP/PKA/RhoA [19], inflammation [10,43], NF-kB/TNFα pathways [16,27], cysteinyl-leukotriene pathway [44] and cyclooxygenase pathway [45].…”
Section: Discussionmentioning
confidence: 98%
“…The depletion of VE-cadherin from endothelial cell membranes is responsible for increased endothelial permeability [19,22,23], which could facilitate the infiltration of pro-atherogenic molecules or cells into the vascular wall. Supporting this hypothesis, we demonstrated, in vitro through an endothelial monolayer, an IH-induced increase in LDL passage (+37%) and monocyte migration (+78%), both being atherogenic mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Polotsky et al, IH-induced changes were found to be HIFdependent. Other studies using HUVECs 31 and HAECs 32 showed increased permeability evidenced by decreased transendothelial electrical resistance and increased expression of vascular endothelial cadherin (VE-cadherin). IH-induced increased permeability in HAECs was both HIF and oxidant dependent 32 .…”
mentioning
confidence: 96%
“…Since EC activation or dysfunction may precede the development of cardiovascular disease, there has been significant interest into determining mechanisms by which OSA affects EC function. Studies evaluating the effects of IH on ECs have shown increased production of pro-inflammatory cytokines, and adhesion molecules consistent with EC activation [28][29][30][31][32][33] . Using gene array, Polotsky et al found that short-term (8 h) exposure to human aortic endothelial cells (HAECs) led to increased expression of pro-inflammatory cytokines particularly IL-8 and NRF2 target genes; however, IH changed neither hypoxia-inducible factor-1α (HIF1A) nor HIF target gene expression 28 .…”
mentioning
confidence: 99%